2017
DOI: 10.1037/pmu0000179
|View full text |Cite
|
Sign up to set email alerts
|

New technology for studying the impact of regular singing and song learning on cognitive function in older adults: A feasibility study.

Abstract: As the proportion of older adults increase, there is a need to investigate ways to promote healthy cognitive aging. There is growing interest in longitudinal studies examining the impact of regular musical activity on nonmusical cognitive functions, but the financial and logistical challenges of such studies greatly limits the amount of research on this topic, especially in older adults. To surmount these challenges and stimulate the pace of research in this area we present a novel technology-based method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Significant wider benefits of singing in later life have been demonstrated (Clift et al, 2008), but there has been limited research focused on ways in which technology can be harnessed to support older people in engaging with singing. Reid et al (2017) adapted a commercially available iPad application (SingFit) and tested its efficacy as a technology-based method for conducting longitudinal studies of regular singing and song learning in older adults. Forty-eight musically inactive participants (i.e., they had not engaged actively with music-making for at least 40 years) aged 65–84 were allocated to singing, listening, or control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant wider benefits of singing in later life have been demonstrated (Clift et al, 2008), but there has been limited research focused on ways in which technology can be harnessed to support older people in engaging with singing. Reid et al (2017) adapted a commercially available iPad application (SingFit) and tested its efficacy as a technology-based method for conducting longitudinal studies of regular singing and song learning in older adults. Forty-eight musically inactive participants (i.e., they had not engaged actively with music-making for at least 40 years) aged 65–84 were allocated to singing, listening, or control groups.…”
Section: Resultsmentioning
confidence: 99%
“…This evidence is in accordance with research concerned with later-life musical engagement more generally, where it has been demonstrated that older learners develop compensatory strategies to mitigate physical or cognitive constraints (Gembris, 2008). Technologies that support receptive musicking (e.g., listening devices) as well as active musicking (e.g., motion sensor devices, digital musical instruments, singing apps and music composition or improvisation technologies) have been found to support access to the multiple personal, social, cognitive, and physical benefits that have been associated with musicking (e.g., Ellis, 2004; Rosseland, 2016; Reid et al, 2017; Vahia et al, 2017). Furthermore, music technologies have been shown to function as creative tools that may have the capacity to provide “restorative spaces” (Jansen, 2005) that privilege reflection and reminiscence, personal healing and problem solving (Duffey et al, 2008; Somody, 2010; Connell, 2012; Lazar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While these areas can be transversal, taking them as a starting point and according to classroom activities, we can categorise the use of the different technological resources as score editors (Bellini, 2008), sequencers and sound generators (Farrimond et al, 2011), audio editors (Silveira & Gavin, 2016), listening training tools (Chan et al, 2006), software for learning to play a musical instrument (Nijs & Leman, 2014; Rowe et al, 2015), developing vocal capacities (Reid et al, 2017) and even audiovisual education resources in the music classroom (Aróstegui, 2010). In these different categories, other types of elements can be transversely included, such as composition using score editors, sequencers, and sound generators and audio editors; coding music using audio editors and sound generators; and so on.…”
Section: Use Of Technology In Music Educationmentioning
confidence: 99%
“…The purpose of the decision tree in the song learning stream (Figure 5) is to promote greater control of the specificity of movement through familiar and structured training. This stream is based upon theories regarding the reported benefits of music for leisure (Särkämö, 2017), familiar song singing (Daykin et al, 2017) and song learning in older adults (Reid, Rakhilin, Patel, Urry & Thomas, 2017). Even though the focus of this music-making stream is to encourage task-specific motor output by learning a song, the wellbeing (Daykin et al, 2017) and rehabilitative benefits of singing (Stegemöller, Radig, Hibbing, Wingate, & Sapienza, 2017) have also been considered.…”
Section: Directed Improvisationmentioning
confidence: 99%